صفات لغة العربية : مشكلة اللغوية وكلماتها - Mohammad Kholison Kholison (Al-Fusha : Arabic Language Education Journal, 2019)
The researchers used the ancient and modern characteristics of the Arabic language, some considered that the features characterized by the Arabic language than other languages. And some considered them as features and descriptions dominated the Arabic language more than dominated the other languages. Some considered it to be an Arabic feature in which other languages ​​shared the same degree. The Arabic language was distinguished by its unique features and characteristics from other languages ​​in the historical, religious and cultural aspects, as well as the linguistic aspects of the voices and disposition, and the meaning and eloquence. It is described in the descriptions and attributes that I have overcome and known, although these features or some of them in other languages ​​to varying degrees, and this is what I mean in this article, as it is very rare that a language has many characteristics that do not exist in a language.